(untitled) (Bangladesh Journal of Medical Science, 2021)
Sudden rapidly increased neck swelling due to spontaneous intranodular bleeding of the thyroid gland is rare occurrence but can be considered. Here, we report an extremely rare case of spontaneous rupture intrathyroidal nodule in a healthy young female who had no history of neck swelling, thyroid disease or neck trauma. She was closely observed and treated conservatively as there was no compromised airway. She was discharged well after completed intravenous antibiotic. Bangladesh Journal of Medical Science Vol.20(3) 2021 p.678-681